2013
DOI: 10.1186/1471-2148-13-1
|View full text |Cite
|
Sign up to set email alerts
|

New approaches for unravelling reassortment pathways

Abstract: BackgroundEvery year the human population encounters epidemic outbreaks of influenza, and history reveals recurring pandemics that have had devastating consequences. The current work focuses on the development of a robust algorithm for detecting influenza strains that have a composite genomic architecture. These influenza subtypes can be generated through a reassortment process, whereby a virus can inherit gene segments from two different types of influenza particles during replication. Reassortant strains are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
219
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(236 citation statements)
references
References 60 publications
16
219
1
Order By: Relevance
“…Vigna Taglianti (1997) and UĂ©no (1998) suggested it may be allied to the European Aphaenops series, contrary to Deuve (1993) who compared Dongodytes with Sinaphaenops UĂ©no & Wang, 1991. Because recent study based on molecular phylogenetic analysis have clearly demonstrated that the Aphaenops series in the widest and traditional sense are restricted to the Pyrenean lineage (Faille et al 2010, 2013), we agree with Deuve’s opinion. Dongodytes seems to be allied to its Chinese congeners such as Sinaphaenops and Pilosaphaenops Deuve & Tian, 2008.…”
Section: Systematicssupporting
confidence: 84%
“…Vigna Taglianti (1997) and UĂ©no (1998) suggested it may be allied to the European Aphaenops series, contrary to Deuve (1993) who compared Dongodytes with Sinaphaenops UĂ©no & Wang, 1991. Because recent study based on molecular phylogenetic analysis have clearly demonstrated that the Aphaenops series in the widest and traditional sense are restricted to the Pyrenean lineage (Faille et al 2010, 2013), we agree with Deuve’s opinion. Dongodytes seems to be allied to its Chinese congeners such as Sinaphaenops and Pilosaphaenops Deuve & Tian, 2008.…”
Section: Systematicssupporting
confidence: 84%
“…The mtDNA haplogroups L0d and L0k have been convincingly shown to be characteristic of autochthonous populations of southern Africa [18], [24], [35]. They therefore represent an ideal measure for detecting admixture in the maternal line between the immigrating Bantu-speaking groups and these autochthonous populations.…”
Section: Resultsmentioning
confidence: 99%
“…Trait-associated measurements of diversification rate utilized the BiSSE model. Even though our ingroup phylogeny was comprehensive, the number of taxa in our data set may not have been large enough to avoid inadequacies of the model [69, 71], which is why we refrain from ascribing statistical significance to these results. Alternate methods of trait-dependant diversification (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Because hypothesis testing in a BiSSE or MuSSE framework can have a high Type I error rate [68–70] and low statistical power when data sets contain fewer than several hundred terminal taxa [71], we refrain from explicitly testing the statistical significance of character-associated variation in model parameter estimates. Instead, we fit models in which each trait was given individual λ , ÎŒ , and q parameters strictly to determine estimates of these model parameters.…”
Section: Methodsmentioning
confidence: 99%